2005
DOI: 10.1159/000083477
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Oxidative Processes in Relation to Renal Disease

Abstract: This article summarizes the biochemical processes that produce reactive oxygen species (ROS) and other mediators that account for ‘oxidative stress’. Formation of ROS in signal transduction cascades is illustrated from studies of kidney cell systems. The pathophysiological implications for the nephrologist are then reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 198 publications
(118 reference statements)
2
36
0
1
Order By: Relevance
“…The major sources of intracellular ROS are the mitochondria, the NADPH-and xanthine-oxidase systems [17]. Our previous study suggests that a major part of Ch-NIC-and oxidant injury-induced intracellular ROS originates in the mitochondria [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The major sources of intracellular ROS are the mitochondria, the NADPH-and xanthine-oxidase systems [17]. Our previous study suggests that a major part of Ch-NIC-and oxidant injury-induced intracellular ROS originates in the mitochondria [6].…”
Section: Discussionmentioning
confidence: 98%
“…Our recent data showed that Ch-NIC may exacerbate IR-AKI-induced oxidative stress by increasing the production of reactive oxygen species (ROS) in proximal tubule cells [6]. While the major sources of intracellular ROS are the mitochondria, the nicotinamide adenine dinucleotide phosphate (NADPH)-and xanthine-oxidase systems [17], our previous study suggests that a major part of Ch-NIC and oxidant injury-induced intracellular ROS originates in the mitochondria [6]. Indeed, Ch-NIC adversely affects mitochondrial function and mitochondrial ROS production [18,19]; however, the mechanism by which it does so is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…When redox homeostasis transitions to redox stress, redox signaling ensues in all tissues and organs regardless of the multiple similar or dissimilar etiologies due to redox stress being a redox signaling system [17, 18]. An elegant discussion of the cellular oxidative processes in renal disease has recently been published for a more in-depth view of these complex mechanisms [19]. …”
Section: Redox Stressmentioning
confidence: 99%
“…In human uremic patients, a state of imbalance between pro‐oxidative and antioxidative processes has been established, and defined as oxidative stress with increased amounts of reactive oxygen species (ROS) present 3, 4, 5. ROS are involved in cell signaling and cause activation of proinflammatory and mitogenic cellular pathways, which enhance the progression of renal fibrosis and cause a progressive decline in renal function 5, 6, 7. Glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase (CAT), and nitric oxide synthase are the most important antioxidant enzymes that detoxify ROS molecules in the kidneys 4…”
mentioning
confidence: 99%